Analisis Manajemen Rantai Pasok (Supply Chain Management) Guna Optimalisasi Distribusi Ayam Broiler untuk Kesejahteraan Peternak Ayam - Hidayat, Nurul; Nover, Catherine; Pagestika, Tria Maha (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Supply Chain Management (SCM) is a strategy that involves various parties in the supply chain to support the long-term functions and overall supply chain within an organization. This research uses a qualitative approach with the researcher as the main instrument, and data is collected through triangulation, namely observation, interviews, and documentation. Observation is crucial in developing the function of broiler chicken farming in Tarakan. Supply Chain Management is applied comprehensively, starting from broiler chicken farming management, processing industries, to marketing, with the aim of running efficient and competitive farming activities, as well as potentially influencing policies in the livestock sector. The problem of this research is how to create efficient work rules to optimize the already optimal supply chain management applied to the distribution system of broiler chicken farming production results, from the production process to reaching consumers' hands, with the aim of achieving maximum profit from the investment made by broiler chicken farming business actors.